EEG measurements and signal processing : sensors, electronic amplification and filtering - Fadzirul Hafiq, Hamzah (Universiti Malaysia Sarawak (UNIMAS), 2017)
This project is based on researching about brainwave and create an electronic device that is EEG which can be used to detect brainwave activity. There are 3 step of doing this project which is the first step is able to design a working circuit that can record a beta wave frequency, and the second step is to build a working device to start measuring the frequency needed and lastly get a result base on real time analysis. Simulation is done while doing the designing to make sure it is working. To get the measurement, the probe from the EEG device is attach to the frontal lobe of the head with one of the probe is attached to the ear to make a grounding. Arduino coding is used to get the final output of the result. For the real time testing, the subject is given a few conditions to get different wave form. First the subject is required to listen to a soft melody and rock music. Then for the second test, the subject is required to watch a video of two type which is the humor video and an action video and lastly the subject is required to read a text. All of the result is than stated and compare.